ANALISIS PERANAN FINTECH DAN E-COMMERCE TERHADAP PERKEMBANGAN UMKM - Hasyim, Tufrida Murniati; Hasibuan, Daniel Roland (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2022)
The purpose of this study is to find out how the role of the fintech business, Financial Technology, and E-commerce in improving the financial performance of micro, small and medium enterprises in the Jakarta, Depo,k and Tangerang areas and to find out how the risks and constraints of Micro, Small and Medium Enterprises in implementing fintech and E-commerce to improve financial performance. The research method in this study is a qualitative descriptive method. From the results of this study, it can be concluded that using fintech and e-commerce is very important for business actors, especially micro, small and medium enterprises, to increase sales and improve the financial performance of their businesses. When income increases, economic performance will certainly increase and improve as well. Improved financial performance can be seen from the profits obtained by micro, small and medium enterprises. In this study, it was also found that there were deficiencies or weaknesses in the use of applications in fintech and e-commerce businesses. The disadvantage of the application system was the lack of socialization and training received by business actors, and at certain periods, it was necessary to update the data on the application, so that prolong the work system of business actors in using or using the application